Missionary Medicine and Sarawak Malay Proselytisation (1848– 1866): The Unfulfilled Mission - Sharifah Sophia, Wan Ahmad (Penerbit USM, 2022)
This article discusses the introduction of the Anglican medical mission in 19th- century Sarawak. Missionary medicine was part of the constellation of Western rationality brought to the Malay Archipelago through colonialism. However, far from being a purely scientific enterprise, missionary medicine became a theological tool for the fulfilment of religious duty expected of the spiritually imbued practitioner engaged by the evangelical society. It was believed that in healing the soul through the body, a conversion could follow. In addition to spiritual conversion, medicine was ideologised as civilisational superior to the indigenous form, therefore should be imposed as a means of civilising the native subjects. To explore the effect of theological medicine on Sarawak Malay, the letters of Bishop Francis Thomas McDougall (1817–1886) became the primary source-material in illuminating the early phase of missionary medicine in Sarawak. The reference to letters as historical evidence was unique as personal correspondence often replete with sentiments. By utilising the history of emotion approach, the sentiment was historicised as a product of the precariousness of life in a colonial situation. It was found that the practice of medicine had been frustrated by the excessive imagination of impending violence, causing the subtle attempt at Malay proselytisation to cease. In the end, missionary medicine had a short lifespan and limited effect on the religious and health belief among Sarawak Malay. To them, Christianity and its medicine were uninspiring and ineffectual.